Modified hydrated filler as well as preparation method and application thereof
By using modified hydration fillers in the low-carbon olefin hydration process, the problems of poor hydrate mixing effect and low-carbon alcohol yield are solved, and more efficient catalysis and lower energy consumption are achieved.
Patent Information
- Application Number
- CN202311218058.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-20
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2043-09-20
AI Technical Summary
In the existing low-carbon olefin hydration process, the hydroene mixing effect is poor, resulting in low-carbon alcohol yield, and the catalyst is prone to sintering and inactivation, high system equipment requirements and large energy consumption.
Modified hydrated filler is used, which is coated with a silane layer, a modified layer A and a modified layer B in sequence from the filler matrix. The modified layers A and B contain specific groups to improve the hydrene mixing effect and catalytic activity.
It significantly improves the mixing effect of hydrene, promotes the increase in yield of low-carbon alcohols, extends the service life of the catalyst, and reduces the energy consumption and equipment requirements of the system.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of low-carbon olefin hydration, and in particular to a modified hydrated filler and a preparation method and application thereof. Background Art
[0002] Olefin hydration is one of the important organic reactions and can be used to prepare alcohols, such as sec-butyl alcohol, isopropyl alcohol, cyclohexanol, etc. Traditional olefin hydration generally adopts sulfuric acid indirect hydration method. This method has serious equipment corrosion problems and waste acid treatment problems, and has gradually been replaced by catalytic direct hydration method. Catalytic direct hydration method generally uses solid acid catalyst to directly generate corresponding low-carbon alcohols from low-carbon olefins. However, since low-carbon olefins are almost immiscible with water, the reaction is a liquid-liquid-solid three-phase system, and the reaction yield is greatly affected by mass transfer efficiency. In order to improve the reaction yield, the catalyst generally used is a modified heat-resistant strong acid ion exchange resin with high reaction activity and good heat resistance, or a zeolite catalyst.
[0003] In order to promote the yield of low-carbon alcohols in the three-phase reaction system, the reaction temperature, reaction pressure, and water-olefin ratio are generally high. However, olefin hydration is a highly exothermic reaction, and it is very easy to produce high temperatures under high reaction temperature conditions, resulting in sintering and deactivation of resin or zeolite catalysts. The high reaction pressure of the system can promote the dissolution of olefins in water, but it has high requirements for equipment and large equipment investment. The increase in the water-olefin ratio is beneficial to the generation of low-carbon alcohols from the perspective of chemical equilibrium, but it will cause a large amount of water circulation in the entire system, a large separation load, and high energy consumption.
[0004] In order to solve the problem of uneven mixing of three phases, the document "Research on the process of preparing sec-butanol by hydration of butene with phase transfer catalysis" (Zhang Yu, Qi Shixue, Journal of Yantai University: Natural Science and Engineering Edition, 2012, No. 2, 111-116) introduced the combination of computer simulation, experimental screening of phase transfer catalysts suitable for butene hydration reaction and process research, and determined that polyethylene glycol is the best phase transfer catalyst suitable for the reaction system. The addition of phase transfer catalyst can significantly improve the single-pass conversion rate of butene hydration (from 5.5% to 6.5%) at higher temperature and water-to-olefin ratio, lower space velocity and appropriate percentage. However, under this reaction condition, the recovery and reuse of phase transfer catalyst and hydrothermal decomposition will lead to complicated process flow and reduced purity of low-carbon alcohol products.
[0005] In the prior art, the direct hydration process of low-carbon olefins using solid acid as a catalyst generally adopts a fixed bed reactor, and the solid acid is loaded in the reactor. The main process is generally to mix the olefin raw material (olefin volume content 80-99%) with the reaction process water, preheat to 70-250°C, and then enter the hydration reactor for reaction. The reaction pressure is 3.0-25.0MPa, and the reaction raw material generates low-carbon alcohol in the reactor bed. The reactor is generally filled with H-type strong acid resin catalyst, and the mixing of materials in the reactor is mainly achieved by the disturbance of the catalyst particle morphology. The H-type strong acid resin catalyst has a strong activity. In addition to the effect on olefin hydration, it also has an effect on the superposition of olefins itself, resulting in olefin polymerization and reducing the yield of low-carbon alcohol. On the other hand, the material mixing is achieved only by the disturbance of the catalyst particles, and the mixing effect is relatively mild and the mixing effect is general. Therefore, the problem of adjusting the catalytic activity, improving the water-olefin mixing effect, and promoting the hydration equilibrium to move to the right has become an urgent problem to be solved in the prior art. Summary of the invention
[0006] The purpose of the present invention is to overcome the problems of poor water-olefin mixing effect and low low-carbon alcohol yield in the low-carbon olefin hydration process in the prior art, and to provide a modified hydration filler and a preparation method and application thereof. The modified hydration filler can significantly improve the water-olefin mixing effect and promote the improvement of the low-carbon alcohol yield.
[0007] In order to achieve the above-mentioned purpose, the first aspect of the present invention provides a modified hydrated filler, wherein the modified hydrated filler includes a filler substrate, a silane layer, a modified layer A and a modified layer B coated on the outer surface of the filler substrate from the inside to the outside; the modified layer A contains pyrrolyl, amide and furanyl; the modified layer B contains phenoxy, pyrrolyl, furanyl, sulfonic acid, phosphoric acid and amide.
[0008] A second aspect of the present invention provides a method for preparing a modified hydrated filler, wherein the method comprises:
[0009] (1) in the presence of a solution containing a silane component, subjecting the outer surface of the filler substrate to a silanization treatment to obtain a filler coated with a silane layer;
[0010] (2) in the presence of a solution containing a modified component A, subjecting the outer surface of the filler coated with the silane layer in step (1) to a modified A treatment to obtain a filler coated with the modified layer A;
[0011] (3) in the presence of a solution containing a modification component B, subjecting the outer surface of the filler coated with the modification layer A in step (2) to a modification B treatment to obtain a modified hydrated filler;
[0012] The modified component A contains pyrrole group, amide group and furan group, and the modified component B contains phenoxy group, pyrrole group, furan group, sulfonic acid group, phosphoric acid group and amide group.
[0013] The third aspect of the present invention provides a use of the modified hydrated filler described in the first aspect or the modified hydrated filler prepared by the preparation method described in the second aspect in the preparation of a low-carbon alcohol aqueous solution by a hydration reaction of low-carbon olefins.
[0014] The inventors of the present invention found in the process of studying the hydration of low-carbon olefins that the olefin hydration is catalyzed by existing solid acid catalysts such as strong acid resins and ZSM-5 molecular sieves, and the olefin single-pass conversion rate is significantly lower than the thermodynamic equilibrium conversion rate, which is mainly affected by factors of mass transfer and chemical equilibrium. Low-carbon olefins are generally difficult to dissolve in water. Even if the water-olefin ratio is greatly excessive, the two are still incompatible. In a fixed bed with a generally low flow rate, the dispersed phase as the oil phase generally exists in the form of large droplets, and the oil-water contact area is small. Even if the water-olefin ratio is increased, it only reduces the dispersion density of the large droplet oil phase under the macroscopic state. From the perspective of the oil-water contact surface, there is basically no obvious change, and there is no obvious driving effect on the rightward movement of the hydration equilibrium, and only a certain dilution effect on the product low-carbon alcohol can be achieved. Solid acid catalysts have good binding properties with water, but poor compatibility with olefins. Olefins are difficult to adsorb on the water-saturated solid acid catalytic surface, which makes it difficult to activate the double bonds. In order to improve the catalytic effect of solid acids, solid acid modification mainly focuses on increasing acid strength and acid density, but this direction will cause side reactions such as olefin superposition, which will lead to reduced yield and selectivity of low-carbon alcohols.
[0015] The low-carbon olefin hydration filler provided by the present invention solves the problems of poor water-olefin mixing effect and low low-carbon alcohol yield in the prior art from a microscopic mechanism. With this filler as the matrix, it is further modified according to the components involved in the hydration reaction, and a silane layer, a modified layer A and a modified layer B are sequentially coated on the outer surface of the filler matrix from the inside to the outside. The silane layer mainly plays the role of a connecting layer, connecting the matrix and the secondary outer modified layer, improving the stability of the secondary outer modified layer and extending the service life of the modified filler. The modified layer A is grafted with an affinity group for the reactant water and a repelling group for the reaction product low-carbon alcohol. A water-rich layer is formed on the outer surface of the matrix through the water-affinity group, providing excess water for the hydration reaction microenvironment, and the low-carbon alcohol present in the modified layer A is pushed to the secondary outer layer through the low-carbon alcohol repelling group on the outer surface.
[0016] The second outer layer of modified layer A is modified layer B, which is the main site of olefin hydration reaction. This layer is grafted with enophilic groups (for enriching olefins), hydrophilic groups (for enriching water), catalytic groups (for activating olefins, and rationally regulating acid strength through coordinated matching of groups), and low-carbon alcohol repelling groups (for transferring low-carbon alcohols generated by the reaction to the outside of the reaction system to promote the hydration reaction to move to the right). Based on the gradient change of hydrophilic strength in modified layer A and modified layer B, water in the main body of the mixed liquid phase is continuously enriched from the main body of the liquid phase to modified layer A. Modified layer B is grafted with enophilic groups that are slightly stronger than the hydrophilic groups. Olefin molecules are continuously captured from the mixed liquid phase through the enophilic groups. Under the activation of catalytic groups with appropriate acid strength, olefins react with water molecules enriched in the surrounding and bottom layers. The low-carbon alcohols generated by hydration are continuously diffused from modified layer B to the main body of the liquid phase under the promotion of low-carbon alcohol repelling groups, thereby moving the hydration equilibrium to the right. The presence of hydrophilic groups in modified layer A and modified layer B achieves a large excess of microscopic water, thereby reducing the water-olefin ratio. The reduction in the water-olefin ratio promotes the enrichment of olefin molecules on the enophilic groups, further promoting the rightward shift of the hydration equilibrium. DETAILED DESCRIPTION
[0017] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0018] In the present invention, the groups and their contents in the modified layer are measured by infrared spectroscopy. The specific test conditions are KBr tableting at 400 cm -1 -4000cm -1 The content of each group in the modified layer is measured step by step during the preparation process.
[0019] In the present invention, the thickness of the modified layer involved is measured by an X-ray fluorescence thickness gauge.
[0020] The first aspect of the present invention provides a modified hydrated filler, wherein the modified hydrated filler includes a filler substrate, a silane layer, a modified layer A and a modified layer B sequentially coated on the outer surface of the filler substrate from the inside to the outside; the modified layer A contains pyrrolyl, amide and furanyl; the modified layer B contains phenoxy, pyrrolyl, furanyl, sulfonic acid, phosphoric acid and amide.
[0021] In the present invention, there is no particular limitation on the preparation method of the filler matrix, and it can be prepared by a method conventionally defined in the art. Preferably, the filler matrix is made by winding and weaving a corrugated wire mesh. According to a specific embodiment of the present invention, the filler matrix is formed by winding layers of corrugated wire mesh. In this preferred embodiment, when the filler rotates around its center at a certain angular velocity, the oil-water mixture sprayed from the distributor arranged at the center of the filler matrix is continuously divided, mixed, and re-divided by the wire mesh during the flow to the surroundings, so that the oil-water mixing effect is greatly improved.
[0022] In the present invention, preferably, the mesh number of the filler matrix is 70-150, the wire diameter is 0.07-0.12 mm, the wire cloth thickness is 0.2-0.5 mm, the peak height is 2-15 mm, and the wave distance is 4-30 mm.
[0023] In the present invention, there is no particular limitation on the material of the filler matrix. Preferably, the filler matrix is made of metal and / or plastic, more preferably metal.
[0024] In the present invention, preferably, the thickness of the silane layer is 7-12 nm.
[0025] In the present invention, preferably, the silane layer is provided by at least one of 2-butenyltriethoxysilane, methylvinyldiethoxysilane and allyldimethoxysilane.
[0026] In the present invention, preferably, based on the surface area of the filler matrix per square meter on a dry basis, the content of pyrrole in the modified layer A is 13-23 mmol / m 2 The content of amide group is 18-38mmol / m 2 The furanyl content is 2.2-5.9mmol / m 2 .
[0027] In the present invention, preferably, the thickness of the modified layer A is 4.5-8.2 nm.
[0028] In the present invention, by selecting the modified layer A with the above group content and thickness, the enrichment of the microscopic reaction raw material water and the driven separation of the reaction product low-carbon alcohol can be achieved.
[0029] In the present invention, preferably, based on the surface area of the filler matrix per square meter of dry basis, the content of phenoxy in the modified layer B is 13-24 mmol / m 2 The content of pyrrolyl is 19-36mmol / m 2 The furanyl content is 3.2-8mmol / m 2 The content of sulfonic acid group is 25-47mmol / m 2 The content of phosphate group is 8.7-24.5mmol / m2 The content of amide group is 12-19mmol / m 2 .
[0030] In the present invention, preferably, the thickness of the modified layer B is 12-20 nm.
[0031] In the present invention, by selecting the modified layer B with the above group content and thickness, the enrichment and activation of the reaction raw materials water and olefins and the driven separation of the reaction product low-carbon alcohols can be achieved, thereby promoting the shift of the equilibrium to the right.
[0032] A second aspect of the present invention provides a method for preparing a modified hydrated filler, wherein the method comprises:
[0033] (1) in the presence of a solution containing a silane component, subjecting the outer surface of the filler substrate to a silanization treatment to obtain a filler coated with a silane layer;
[0034] (2) in the presence of a solution containing a modified component A, subjecting the outer surface of the filler coated with the silane layer in step (1) to a modified A treatment to obtain a filler coated with the modified layer A;
[0035] (3) in the presence of a solution containing a modifying component B, subjecting the outer surface of the filler coated with the modified layer A in step (2) to a modification B treatment to obtain a modified hydrated filler coated with the modified layer B;
[0036] The modified component A contains pyrrole group, amide group and furan group, and the modified component B contains phenoxy group, pyrrole group, furan group, sulfonic acid group, phosphoric acid group and amide group.
[0037] In the present invention, the type, material, characteristic parameters and preparation method of the filler matrix in step (1) have been described in the first aspect and will not be repeated here.
[0038] In the present invention, preferably, in step (1), the conditions of the silanization treatment and the amount of the solution containing the silane component are such that the thickness of the silane layer is 7-12 nm.
[0039] In the present invention, there is no particular limitation on the method of silanization treatment. Preferably, the silanization treatment comprises: contacting and immersing the solution containing the silane component with the outer surface of the filler matrix, and then drying and curing.
[0040] In the present invention, there is no particular limitation on the conditions for the silanization treatment. Preferably, the contact immersion treatment conditions include: an immersion temperature of 30-60°C, a time of 1.5-3h, and a liquid-to-solid volume of 1-3.
[0041] In the present invention, there is no particular limitation on the drying and curing conditions. Preferably, the drying and curing conditions include: a temperature of 105-125° C. and a time of 30-60 min.
[0042] In the present invention, preferably, in step (1), the solution containing the silane component is obtained by mixing a silane reagent, water and a low-carbon alcohol and pre-hydrolyzing them.
[0043] In the present invention, preferably, the volume ratio of silane reagent: water: low carbon alcohol is (2.2-5.2): (3.5-5.9): (89-95).
[0044] In the present invention, preferably, the pre-hydrolysis time is 15-30 hours.
[0045] In the present invention, preferably, the pH of the solution containing the silane component is 7.5-8.5.
[0046] In the present invention, preferably, the silane reagent is selected from at least one of 2-butenyltriethoxysilane, methylvinyldiethoxysilane and allyldimethoxysilane.
[0047] In the present invention, preferably, based on the surface area of the filler matrix per square meter on a dry basis, the content of pyrrole in the modified layer A is 13-23 mmol / m 2 The content of amide group is 18-38mmol / m 2 The furanyl content is 2.2-5.9mmol / m 2 .
[0048] In the present invention, preferably, in step (2), the thickness of the modified layer A is 4.5-8.2 nm.
[0049] In the present invention, there is no particular limitation on the method of the modification A treatment. Preferably, in step (2), the modification A treatment comprises: immersing a solution containing the modification component A into contact with the outer surface of the filler coated with the silane layer in step (1).
[0050] In the present invention, preferably, in step (2), the solution containing modified component A comprises modified component A, a first initiator and a first solvent, wherein the mass ratio of modified component A: first initiator: first solvent is (4.5-7.9): (0.1-0.4): (93-97).
[0051] In the present invention, there is no particular limitation on the type of the first solvent. Preferably, in step (2), the first solvent is selected from at least one of toluene, p-xylene, m-xylene and o-xylene.
[0052] In the present invention, there is no particular limitation on the type of the first initiator. Preferably, in step (2), the first initiator is selected from at least one of azo, organic peroxide, inorganic peroxide and redox initiators, preferably at least one of azobisisobutyronitrile, benzoyl peroxide, potassium persulfate and hydrogen peroxide, more preferably benzoyl peroxide.
[0053] In the present invention, preferably, in step (2), the modified component A contains pyrrole derivatives, amide derivatives, and furan derivatives, wherein the molar ratio of pyrrole derivatives: amide derivatives: furan derivatives is (15-27): (21-44): (2.7-6.8).
[0054] In the present invention, preferably, the pyrrol group is provided by a pyrrole derivative, preferably by at least one of 3-isopropenyl-1-methyl-pyrrole, 1-(3-butene-1-yl)-2-vinyl-1H-pyrrole and 5-allyl-4-methoxy-1,5-dihydro-2H-pyrrol-2-one.
[0055] In the present invention, preferably, the amide group is provided by an amide derivative, preferably provided by at least one of N,N'-dihydroxyethylbisacrylamide, N,N-methylenebisacrylamide and hexamethylenebisacrylamide.
[0056] In the present invention, preferably, the furanyl group is provided by a furan derivative, preferably by 2-(1-propen-2-yl)furan and / or 2-(2-pentenyl)furan.
[0057] In the present invention, there is no particular limitation on the conditions for the treatment of modification A. Preferably, in step (2), the conditions for the treatment of modification A include: a liquid-to-solid volume ratio of 1-3, a treatment temperature of 60-80°C, and a treatment time of 1.5-3h.
[0058] In the present invention, preferably, based on the surface area of the filler matrix per square meter on a dry basis, the content of phenoxy in the modified layer B is 13-24 mmol / m 2 The content of pyrrolyl is 19-36mmol / m 2 The furanyl content is 3.2-8mmol / m 2 The content of sulfonic acid group is 25-47mmol / m 2 The content of phosphate group is 8.7-24.5mmol / m 2 The content of amide group is 12-19mmol / m 2 .
[0059] In the present invention, preferably, the thickness of the modified layer B is 12-20 nm.
[0060] In the present invention, there is no particular limitation on the method of the modified B treatment. Preferably, in step (3), the modified B treatment comprises: immersing a solution containing the modified component B in contact with the outer surface of the filler coated with the modified layer A in step (2).
[0061] In the present invention, preferably, in step (3), the solution containing modified component B contains modified component B, a second initiator and a second solvent, wherein the mass ratio of modified component B: second initiator: second solvent is (5.5-10.4): (0.1-0.5): (92-96).
[0062] In the present invention, preferably, in step (3), the modified component B contains phenoxy derivatives, pyrrole derivatives, furan derivatives, sulfonic acid derivatives, phosphoric acid derivatives, and amide derivatives, wherein the molar ratio of phenoxy derivatives: pyrrole derivatives: furan derivatives: sulfonic acid derivatives: phosphoric acid derivatives: amide derivatives is (15-29): (22-43): (3.9-9.5): (30-56): (10.3-28.9): (14.3-22.7).
[0063] In the present invention, preferably, the phenoxy group is provided by a phenoxy derivative, preferably provided by at least one of 4-methoxystyrene, allylphenyl ether and phenyl vinyl ether.
[0064] In the present invention, preferably, the phosphate group is provided by a phosphate derivative, preferably by at least one of (2-fluoro-3,7-dimethyloct-1,6-dien-3-yl)phosphonyl hydrogen phosphate, [2-methyl-2-(4-methylpent-3-enyl)cyclopropyl]methylphosphonyl hydrogen phosphate and 2-(phosphoryloxy)propane-1,3-diyl dimethacrylate.
[0065] In the present invention, preferably, the sulfonic acid group is provided by a sulfonic acid derivative, preferably by at least one of 4-hydroxy-6-(prop-2-enoylamino)naphthalene-2-sulfonic acid, (Z)-4',4"'-(ethylene-1,2-diyl)bis(([[1,1'-biphenyl]-4-sulfonic acid)) and 4-{(E)-2-[3,5-di(sulfooxy)phenyl]vinyl}phenyl hydrosulfate.
[0066] In the present invention, the pyrrolyl group, amide group and furanyl group are provided by their corresponding derivatives, and the specific types of the derivatives have been described in the above content and will not be repeated here.
[0067] In the present invention, there is no particular limitation on the conditions for the treatment of modified B. Preferably, in step (3), the conditions for the treatment of modified B include: a liquid-to-solid volume ratio of 1-3, a treatment temperature of 70-90°C, and a treatment time of 1.5-3h.
[0068] In the present invention, preferably, step (3) further comprises subjecting the modified B treated product to post-modification treatment in a post-modification treatment agent. In the present invention, there is no particular limitation on the post-modification treatment method, and preferably, the post-modification treatment is performed by immersion.
[0069] In the present invention, there is no particular limitation on the type of the post-modification treatment agent. Preferably, the post-modification treatment agent is selected from at least one of ethanol, acetone and methanol, and more preferably ethanol.
[0070] In the present invention, there is no particular limitation on the post-modification treatment conditions. Preferably, the post-modification treatment conditions include: a treatment time of 0.5-1 h.
[0071] In the present invention, preferably, the post-modification treatment further comprises drying the post-modification treatment product. Preferably, the drying treatment is performed under a nitrogen atmosphere.
[0072] In the present invention, preferably, the conditions of the drying treatment include: a drying temperature of 100-120° C. and a drying time of 0.5-1 h.
[0073] The third aspect of the present invention provides a use of the modified hydrated filler described in the first aspect or the modified hydrated filler prepared by the preparation method described in the second aspect in the preparation of a low-carbon alcohol aqueous solution by a hydration reaction of low-carbon olefins.
[0074] In the present invention, preferably, the raw materials for the hydration reaction of light olefins include reaction raw materials containing light olefins and water.
[0075] In the present invention, preferably, the reaction raw material containing low-carbon olefins contains C3 and / or C4 low-carbon olefins.
[0076] In the present invention, preferably, based on the reaction raw material containing light olefins, the content of light olefins is 10-100% by volume, and more preferably 25-95% by volume.
[0077] In the present invention, there is no particular limitation on the contact mode of the hydration reaction of low-carbon olefins. Preferably, the reaction raw materials containing low-carbon olefins and water are mixed in the modified hydration filler described in the first aspect or the third aspect and contacted with the outer surface of the modified hydration filler to carry out the hydration reaction of low-carbon olefins to obtain an aqueous solution containing low-carbon alcohols; further preferably, the contact includes the mixture of the reaction raw materials containing low-carbon olefins and water entering the modified hydration filler through the modified hydration filler material distributor and contacting with the outer surface of the modified hydration filler.
[0078] In the present invention, preferably, the modified hydrated filler has a supergravity factor of 100-200 during operation.
[0079] In the present invention, preferably, the conditions for the hydration reaction of the light olefins include: a temperature of 100-160°C, a pressure of 1000-3000 kPa on a gauge pressure, and a volume space velocity of 0.1-0.3 seconds for the mixture of the reaction raw materials containing the light olefins and water based on the macroscopic volume of the modified hydrated filler. -1 , the molar ratio of water to olefin reaction raw material is 2-6.
[0080] In the present invention, preferably, the single-pass olefin conversion rate of the low-carbon olefin hydration is greater than 60%, and the selectivity of the low-carbon alcohol is greater than 95%.
[0081] In the present invention, the content of each group in the olefin hydration microchannel is measured by the test method described above.
[0082] In the present invention, component analysis adopts 20A high performance liquid chromatography system (Shimadzu Corporation, Japan, equipped with autosampler, 10AT and 10AD pumps, 20A multi-wavelength ultraviolet detector); ACQUITY UPLC / Xevo G2 QTOF ultra-high performance liquid chromatography high-resolution tandem mass spectrometry (Waters Corporation, USA, equipped with autosampler, diode array ultraviolet detector). High performance liquid chromatography conditions: chromatographic column: Zorbax Eclipse Plus C18 (4.6mm×150mm, 5μm), mobile phase: water (containing 0.06%v phosphoric acid): acetonitrile = 95:5, flow rate: 1.0mL / min, detection wavelength: 210nm, column temperature: 35°C, injection volume: 1μL. Ultra-high performance liquid chromatography conditions: chromatographic column: HSS T3 (2.1 mm × 100 mm, 1.7 μm); mobile phase: water, methanol; gradient elution (positive ion mode): 0 min V (water): V (methanol) = 85:15, 2.5 min later V (water): v (methanol) = 55:35, 4 min later V (water): V (methanol): 10:90, flow rate: 0.45 mL / min; gradient elution (negative ion mode): 0 min V (water): V (methanol): 70:30, 2.5 min later V (water): V (methanol) = 55:35, 3.5 min later V (water): V (methanol) = 10:90; flow rate: 0.45 mL / min; column temperature: 30 ° C; injection volume: 3 μL. Mass spectrometry conditions: electrospray ionization source (ESI), positive or negative ion scanning mode, capillary voltage 2 kV, cone voltage 30 eV, ion source temperature: 120 ° C, desolvation temperature 450 ° C, cone gas flow rate 50 L / h, desolvation gas (N2) flow rate 900 L / h.
[0083] The present invention will be described in detail below through examples.
[0084] Example 1
[0085] The composition of the reaction raw materials containing light olefins in this embodiment includes, by volume percentage, 30.5% of isobutane, 8.2% of normal butane, 59.6% of normal butene, and 1.7% of pentane.
[0086] In this embodiment, the filler matrix is prepared by the following method: a corrugated wire mesh is obtained by a weaving process, and then the filler matrix is obtained by winding along the central axis. The wire mesh number of the filler matrix is 120, the wire diameter is 0.1 mm, the wire cloth thickness is 0.3 mm, the peak height is 8.5 mm, and the wave distance is 17 mm. The material of the filler is metal.
[0087] In step (1), the silane component solution is contacted with the filler matrix, and then dried and cured to form a silane layer on the outer surface of the filler. The contact conditions are immersion at a liquid-to-solid volume ratio of 2, a treatment temperature of 45°C, and a treatment time of 2.3h. The drying temperature is 118°C and the drying time is 45 minutes. Drying is carried out under a protective atmosphere of nitrogen. The silane component solution is obtained by mixing a silane reagent, water and anhydrous low-carbon alcohol, and then pre-hydrolyzing. The pre-hydrolysis time is 22 hours. The volume ratio of silane reagent: water: anhydrous low-carbon alcohol is 3.7:4.5:93. The pH value of the silane component solution is 7.9. The silane reagent is methylvinyldiethoxysilane. The anhydrous low-carbon alcohol is anhydrous methanol. The amount of silane component solution used is such that the thickness of the silane layer is 9.6nm.
[0088] In step (2), a solution containing modified component A is brought into contact with the outer surface of a filler coated with a silane layer, so that the outer surface of the filler coated with the silane layer is coated with modified layer A. In the solution containing modified component A, the mass ratio of modified component A: first initiator: first solvent is 6.2:0.2:95. The first solvent is toluene. The first initiator is benzoyl peroxide. Modified component A contains pyrrole derivatives, amide derivatives, and furan derivatives, wherein the molar ratio of pyrrole derivatives: amide derivatives: furan derivatives is 21.2:32.4:4.7. Pyrrole derivatives are provided by 1-(3-butene-1-yl)-2-vinyl-1H-pyrrole. Furan derivatives are provided by 2-(1-propylene-2-yl) furan. Amide derivatives are provided by N,N-methylenebisacrylamide. The treatment conditions of modification A include: the solution containing the modified component A is in contact with the outer surface of the filler coated with the silane layer in step (1), the liquid-to-solid volume ratio is 2, the treatment temperature is 70°C, and the treatment time is 2.3 hours. Based on the surface area of the filler matrix per square meter of dry basis, the content of pyrrole in the modified layer A is 17.8 mmol / m 2 The content of amide group is 27.2mmol / m 2 The furanyl content is 3.9mmol / m 2 The thickness of the modified layer A is 6.4 nm.
[0089] In step (3), the solution containing modified component B is brought into contact with the outer surface of the filler coated with modified layer A in step (2), so that the outer surface of the filler coated with modified layer A is coated with modified layer B. In the solution containing modified component B, the mass ratio of modified component B: second initiator: second solvent is 7.9:0.3:94. The second solvent is toluene. Modified component B contains phenoxy derivatives, pyrrole derivatives, furan derivatives, sulfonic acid derivatives, phosphoric acid derivatives, and amide derivatives, wherein the molar ratio of phenoxy derivatives: pyrrole derivatives: furan derivatives: sulfonic acid derivatives: phosphoric acid derivatives: amide derivatives is 21.8:32.4:6.6:43.1:19.5:18.4. Phenoxy derivatives are provided by allyl phenyl ether. Pyrrole derivatives are provided by 1-(3-butene-1-yl)-2-vinyl-1H-pyrrole. The furan derivative is provided by 2-(1-propylene-2-yl)furan. The amide derivative is provided by N,N-methylenebisacrylamide. The phosphoric acid derivative is provided by [2-methyl-2-(4-methylpent-3-enyl)cyclopropyl]methylphosphonic acid hydrogen phosphate. The sulfonic acid derivative is provided by (Z)-4',4"'-(ethylene-1,2-diyl)bis(([[1,1'-biphenyl]-4-sulfonic acid)). The second initiator is benzoyl peroxide. The treatment conditions for modification B include: a solution containing the modified component B is contacted with the outer surface of the filler coated with the modified layer A in step (2), the liquid-to-solid volume ratio is 2, the treatment temperature is 80°C, and the treatment time is 2.3h. Based on the surface area of the dry filler matrix per square meter, the content of phenoxy in the modified layer B is 18.4mmol / m 2 The content of pyrrolyl is 27.3mmol / m 2 The furanyl content is 5.6mmol / m 2 The content of sulfonic acid group is 36.4mmol / m 2 The content of phosphate group is 16.4mmol / m 2 The content of amide group is 15.5mmol / m 2 The thickness of the modified layer B was 15.8 nm.
[0090] Step (3) further comprises subjecting the modified B treated product to post-modification treatment in a post-modification treatment agent. The post-modification treatment agent is anhydrous ethanol. The post-modification treatment conditions include: soaking treatment time of 0.7h, drying temperature of 110°C, and drying time of 0.7h.
[0091] The modified hydrated filler prepared in this embodiment is used in the hydration of low-carbon olefins. A filler bed is used. The supergravity factor of the modified hydrated filler during operation is 150. The water-olefin mixture flows in a manner such that the reaction raw materials containing olefins and desalted water are sprayed from the center of the modified hydrated filler to the periphery. The reaction raw materials containing olefins and desalted water are mixed in the modified hydrated filler and contact with the outer surface of the modified hydrated filler to perform a hydration reaction, thereby obtaining an aqueous solution containing low-carbon alcohols.
[0092] The olefin hydration reaction conditions include: a temperature of 130°C, a pressure of 2000 kPa on a gauge pressure, a volume space velocity of 0.2 seconds for a mixture of a reaction raw material containing a low carbon olefin and water based on the macroscopic volume of the modified hydration filler. -1 , the molar ratio of water to olefin reaction raw material is 4.
[0093] The single-pass olefin conversion rate of olefin hydration is 68.2%, and the selectivity for low-carbon alcohols is 96.7%.
[0094] Example 2
[0095] The same reaction raw materials containing light olefins as in Example 1 were selected.
[0096] In this embodiment, the filler matrix is prepared by the following method: a corrugated wire mesh is obtained by a weaving process, and then the filler matrix is obtained by winding along the central axis. The wire mesh number of the filler matrix is 140, the wire diameter is 0.08 mm, the wire cloth thickness is 0.3 mm, the peak height is 3 mm, and the wave distance is 5 mm. The material of the filler is metal.
[0097] In step (1), the silane component solution is contacted with the filler matrix, and then dried and cured to form a modified layer A on the outer surface of the filler. The contact conditions are: immersion at a liquid-to-solid volume ratio of 3, a treatment temperature of 57°C, and a treatment time of 2.7h. The drying temperature is 123°C and the drying time is 56 minutes. Drying is carried out under a protective atmosphere of nitrogen. The silane component solution is obtained by mixing a silane reagent, water and anhydrous low-carbon alcohol, and then pre-hydrolyzing. The pre-hydrolysis time is 29 hours. The volume ratio of silane reagent: water: anhydrous low-carbon alcohol is 5.1:5.6:92. The pH value of the silane component solution is 8.2. The silane reagent is methylvinyldiethoxysilane. The anhydrous low-carbon alcohol is anhydrous methanol. The amount of silane component solution used is such that the thickness of the silane layer is 11.3nm.
[0098] In step (2), a solution containing modified component A is brought into contact with the outer surface of a filler coated with a silane layer, so that the outer surface of the filler coated with the silane layer is coated with modified layer A. In the solution containing modified component A, the mass ratio of modified component A: first initiator: first solvent is 7.8:0.3:94. The first solvent is toluene. The first initiator is benzoyl peroxide. Modified component A contains pyrrole derivatives, amide derivatives, and furan derivatives, wherein the molar ratio of pyrrole derivatives: amide derivatives: furan derivatives is 26:43:6.7. Pyrrole derivatives are provided by 1-(3-butene-1-yl)-2-vinyl-1H-pyrrole. Furan derivatives are provided by 2-(1-propylene-2-yl) furan. Amide derivatives are provided by N,N-methylenebisacrylamide. The treatment conditions of modification A include: a solution containing the modified component A is contacted with the outer surface of the filler coated with the silane layer in step (1), the liquid-to-solid volume ratio is 3, the treatment temperature is 79°C, and the treatment time is 2.7 hours. Based on the surface area of the filler matrix per square meter of dry basis, the content of pyrrole in the modified layer A is 22.6 mmol / m 2 The content of amide group is 37.4mmol / m 2 The furanyl content is 5.8mmol / m 2 The thickness of the modified layer A was 7.9 nm.
[0099] In step (3), the solution containing modified component B is brought into contact with the outer surface of the filler coated with modified layer A in step (2), so that the outer surface of the filler coated with modified layer A is coated with modified layer B. In the solution containing modified component B, the mass ratio of modified component B: second initiator: second solvent is 10.2:0.4:93. The second solvent is toluene. Modified component B contains phenoxy derivatives, pyrrole derivatives, furan derivatives, sulfonic acid derivatives, phosphoric acid derivatives, and amide derivatives, wherein the molar ratio of phenoxy derivatives: pyrrole derivatives: furan derivatives: sulfonic acid derivatives: phosphoric acid derivatives: amide derivatives is 28:42:9.4:55:28.6:22.5. Phenoxy derivatives are provided by allyl phenyl ether. Pyrrole derivatives are provided by 1-(3-butene-1-yl)-2-vinyl-1H-pyrrole. Furan derivatives are provided by 2-(1-propylene-2-yl) furan. The amide derivatives are provided by N,N-methylenebisacrylamide. The phosphoric acid derivatives are provided by [2-methyl-2-(4-methylpent-3-enyl)cyclopropyl]methylphosphonic acid hydrogen phosphate. The sulfonic acid derivatives are provided by (Z)-4',4"'-(ethylene-1,2-diyl)bis(([[1,1'-biphenyl]-4-sulfonic acid)). The second initiator is benzoyl peroxide. The treatment conditions for modification B include: a solution containing the modified component B is contacted with the outer surface of the filler coated with the modified layer A in step (2), the liquid-to-solid volume ratio is 3, the treatment temperature is 88°C, and the treatment time is 2.6h. Based on the surface area of the filler matrix per square meter on a dry basis, the content of phenoxy in the modified layer B is 23.6mmol / m 2 The content of pyrrolyl is 35.4mmol / m 2 The furanyl content is 7.9mmol / m 2 The content of sulfonic acid group is 46.3mmol / m 2 The content of phosphate group is 24.1mmol / m 2 The content of amide group is 18.9mmol / m 2 The thickness of the modified layer B was 19.1 nm.
[0100] Step (3) further comprises subjecting the modified B treated product to post-modification treatment in a post-modification treatment agent. The post-modification treatment agent is anhydrous ethanol. The post-modification treatment conditions include: soaking treatment time of 0.8h, drying temperature of 116°C, and drying time of 0.9h.
[0101] According to the reaction method of Example 1, the modified hydrated filler has a supergravity factor of 180 during operation.
[0102] The conditions for the olefin hydration reaction include: a temperature of 110°C, a pressure of 1500 kPa on a gauge pressure, a volume space velocity of 0.1 s / min based on the macroscopic volume of the modified hydration filler, and a mixture of the reaction raw material containing the light olefin and water. -1 , the molar ratio of water to olefin reaction raw material is 5.
[0103] The single-pass olefin conversion rate of olefin hydration is 73.2%, and the selectivity for low-carbon alcohols is 97.3%.
[0104] Example 3
[0105] The same olefin-containing reaction raw material as in Example 1 was selected.
[0106] In this embodiment, the filler matrix is prepared by the following method: a corrugated wire mesh is obtained by a weaving process, and then the filler matrix is obtained by winding along the central axis. The wire mesh number of the filler matrix is 80, the wire diameter is 0.11 mm, the wire cloth thickness is 0.4 mm, the peak height is 12 mm, and the wave distance is 20 mm. The material of the filler is metal.
[0107] In step (1), the silane component solution is contacted with the filler matrix, and then dried and cured to form a modified layer A on the outer surface of the filler. The contact conditions are: immersion at a liquid-to-solid volume ratio of 1, a treatment temperature of 32°C, and a treatment time of 1.7h. The drying temperature is 112°C, and the drying time is 34 minutes. Drying is carried out under a protective atmosphere of nitrogen. The silane component solution is obtained by mixing a silane reagent, water, and anhydrous low-carbon alcohol, and then pre-hydrolyzing. The pre-hydrolysis time is 15 hours. The volume ratio of silane reagent: water: anhydrous low-carbon alcohol is 2.4:3.3:95. The pH value of the silane component solution is 7.8. The silane reagent is methylvinyldiethoxysilane. The anhydrous low-carbon alcohol is anhydrous methanol. The amount of silane component solution used is such that the thickness of the silane layer is 8.2nm.
[0108] In step (2), a solution containing modified component A is brought into contact with the outer surface of a filler coated with a silane layer, so that the outer surface of the filler coated with the silane layer is coated with modified layer A. In the solution containing modified component A, the mass ratio of modified component A: first initiator: first solvent is 4.7:0.2:96. The first solvent is toluene. The first initiator is benzoyl peroxide. Modified component A contains pyrrole derivatives, amide derivatives, and furan derivatives, wherein the molar ratio of pyrrole derivatives: amide derivatives: furan derivatives is 16.2:21.8:2.8. Pyrrole derivatives are provided by 1-(3-butene-1-yl)-2-vinyl-1H-pyrrole. Furan derivatives are provided by 2-(1-propylene-2-yl) furan. Amide derivatives are provided by N,N-methylenebisacrylamide. The treatment conditions of modification A include: the solution containing the modified component A is in contact with the outer surface of the filler coated with the silane layer in step (1), the liquid-to-solid volume ratio is 1, the treatment temperature is 62°C, and the treatment time is 1.7 hours. Based on the surface area of the filler matrix per square meter of dry basis, the content of pyrrole in the modified layer A is 13.8 mmol / m 2 The content of amide group is 18.6mmol / m 2 The furanyl content is 2.4mmol / m 2 The thickness of the modified layer A is 4.6 nm.
[0109] In step (3), the solution containing modified component B is brought into contact with the outer surface of the filler coated with modified layer A in step (2), so that the outer surface of the filler coated with modified layer A is coated with modified layer B. In the solution containing modified component B, the mass ratio of modified component B: second initiator: second solvent is 5.7:0.2:95. The second solvent is toluene. Modified component B contains phenoxy derivatives, pyrrole derivatives, furan derivatives, sulfonic acid derivatives, phosphoric acid derivatives, and amide derivatives, wherein the molar ratio of phenoxy derivatives: pyrrole derivatives: furan derivatives: sulfonic acid derivatives: phosphoric acid derivatives: amide derivatives is 15.8:22.4:4.1:32:10.4:14.5. Phenoxy derivatives are provided by allyl phenyl ether. Pyrrole derivatives are provided by 1-(3-butene-1-yl)-2-vinyl-1H-pyrrole. The furan derivative is provided by 2-(1-propylene-2-yl)furan. The amide derivative is provided by N,N-methylenebisacrylamide. The phosphoric acid derivative is provided by [2-methyl-2-(4-methylpent-3-enyl)cyclopropyl]methylphosphonic acid hydrogen phosphate. The sulfonic acid derivative is provided by (Z)-4',4"'-(ethylene-1,2-diyl)bis(([[1,1'-biphenyl]-4-sulfonic acid)). The second initiator is benzoyl peroxide. The treatment conditions for modification B include: a solution containing the modified component B is contacted with the outer surface of the filler coated with the modified layer A in step (2), the liquid-to-solid volume ratio is 1, the treatment temperature is 72°C, and the treatment time is 1.6h. Based on the surface area of the dry filler matrix per square meter, the content of phenoxy in the modified layer B is 13.9mmol / m 2 The content of pyrrolyl is 19.7mmol / m 2 The furanyl content is 3.6mmol / m 2 The content of sulfonic acid group is 28.1mmol / m 2 The content of phosphate group is 9.1mmol / m 2 The content of amide group is 12.7mmol / m 2 The thickness of the modified layer B was 12.7 nm.
[0110] Step (3) further comprises subjecting the modified B treated product to post-modification treatment in a post-modification treatment agent. The post-modification treatment agent is anhydrous ethanol. The post-modification treatment conditions include: soaking treatment time of 0.6h, drying temperature of 104°C, and drying time of 0.6h.
[0111] According to the reaction method of Example 1, the modified hydrated filler has a supergravity factor of 120 during operation.
[0112] The conditions for the olefin hydration reaction include: a temperature of 150°C, a pressure of 2600 kPa on a gauge pressure, a volume space velocity of 0.3 seconds for a mixture of the reaction raw material containing the light olefin and water based on the macroscopic volume of the modified hydration filler. -1 , the molar ratio of water to olefin reaction raw material is 3.
[0113] The single-pass olefin conversion rate of olefin hydration is 62.7%, and the selectivity for low-carbon alcohols is 95.8%.
[0114] Example 4
[0115] The method of Example 2 is followed, except that the reaction raw materials containing light olefins in this example include, by volume percentage, 16.4% isobutane, 7.3% normal butane, 74.9% normal butene, and 1.4% pentane.
[0116] According to the reaction method and conditions of Example 2, the single-pass olefin conversion rate of olefin hydration was 74.6%, and the selectivity of low-carbon alcohols was 97.5%.
[0117] Example 5
[0118] The method of Example 2 is followed, except that the reaction raw materials containing light olefins in this example include, by volume percentage, 6.8% isobutane, 2.2% normal butane, 90.5% normal butene, and 0.5% pentane.
[0119] According to the reaction method and conditions of Example 2, the single-pass olefin conversion rate of olefin hydration was 75.3%, and the selectivity of low-carbon alcohols was 97.6%.
[0120] Example 6
[0121] The method of Example 2 is followed, except that the reaction raw materials containing light olefins in this example include, by volume percentage, 50.8% isobutane, 13.7% n-butane, 30.0% n-butene, and 5.5% pentane.
[0122] According to the reaction method and conditions of Example 2, the single-pass olefin conversion rate of olefin hydration was 70.3%, and the selectivity of low-carbon alcohols was 97.1%.
[0123] Comparative Example 1
[0124] The same reaction raw materials containing light olefins as those in Example 5 were selected, namely, by volume percentage, they included: 6.8% isobutane, 2.2% normal butane, 90.5% normal butene, and 0.5% pentane.
[0125] The olefin hydration reactor is filled with Suqing brand SQD-69 styrene macroporous strong acid cation exchange resin, the reaction temperature is 155℃, the reaction pressure is 78 kg, and the reaction mass space velocity is 1h -1The single-pass conversion rate of n-butene was 11.03% and the selectivity was 95.7%.
[0126] Comparative Example 2
[0127] The method of Example 3 is followed, except that in this comparative example, the substrate after silanization treatment (i.e., the silane reagent solution is contacted with the filler substrate and then dried and solidified) is directly contacted with the outer surface of the filler coated with the silane layer using a solution containing the modified component B, and no longer goes through the process of contacting the outer surface of the silanized filler with a solution containing the modified component A, and the subsequent modification post-treatment is omitted.
[0128] According to the reaction method and conditions of Example 3, in the olefin hydration reactor, the single-pass olefin conversion rate of olefin hydration was 37.6%, and the selectivity of low-carbon alcohols was 87.3%.
[0129] Comparative Example 3
[0130] The method of Example 3 is followed, except that the filler matrix that has not been modified is directly used in this comparative example.
[0131] According to the reaction method and conditions of Example 3, in the olefin hydration reactor, the single-pass olefin conversion rate of olefin hydration was 1.8%, and the selectivity of low-carbon alcohols was 85.2%.
[0132] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A modified hydrated filler, characterized in that: The modified hydrated filler comprises a filler matrix, a silane layer, a modified layer A and a modified layer B which are sequentially coated on the outer surface of the filler matrix from the inside to the outside; the modified layer A contains pyrrolyl, amide and furanyl; the modified layer B contains phenoxy, pyrrolyl, furanyl, sulfonic acid, phosphoric acid and amide.
2. The modified hydrated filler according to claim 1, wherein: The filler matrix is made by winding and weaving a corrugated wire mesh; Preferably, the mesh number of the filler matrix is 70-150, the wire diameter is 0.07-0.12 mm, the wire cloth thickness is 0.2-0.5 mm, the peak height is 2-15 mm, and the wave distance is 4-30 mm; And / or, the filler matrix is made of metal and / or plastic, preferably metal.
3. The modified hydrated filler according to claim 1 or 2, wherein: The thickness of the silane layer is 7-12 nm; And / or, the silane layer is provided by at least one of 2-butenyltriethoxysilane, methylvinyldiethoxysilane and allyldimethoxysilane.
4. The modified hydrated filler according to claim 1 or 2, wherein: Based on the surface area of the filler matrix per square meter of dry basis, the content of pyrrole in the modified layer A is 13-23 mmol / m 2 The content of amide group is 18-38mmol / m 2 The furanyl content is 2.2-5.9mmol / m 2 ; And / or, the thickness of the modified layer A is 4.5-8.2 nm.
5. The modified hydrated filler according to claim 1 or 2, wherein: Based on the surface area of the filler matrix per square meter, the content of phenoxy in the modified layer B is 13-24mmol / m 2 The content of pyrrolyl is 19-36mmol / m 2 The furanyl content is 3.2-8mmol / m 2 The content of sulfonic acid group is 25-47mmol / m 2 The content of phosphate group is 8.7-24.5mmol / m 2 The content of amide group is 12-19mmol / m 2 ; And / or, the thickness of the modified layer B is 12-20 nm.
6. A method for preparing a modified hydrated filler, wherein: The method includes: (1) in the presence of a solution containing a silane component, subjecting the outer surface of the filler substrate to a silanization treatment to obtain a filler coated with a silane layer; (2) in the presence of a solution containing a modified component A, subjecting the outer surface of the filler coated with the silane layer in step (1) to a modified A treatment to obtain a filler coated with the modified layer A; (3) in the presence of a solution containing a modification component B, subjecting the outer surface of the filler coated with the modification layer A in step (2) to a modification B treatment to obtain a modified hydrated filler; The modified component A contains pyrrole group, amide group and furan group, and the modified component B contains phenoxy group, pyrrole group, furan group, sulfonic acid group, phosphoric acid group and amide group.
7. The method according to claim 6, wherein: In step (1), the filler matrix is made by winding and weaving a corrugated wire mesh; Preferably, the mesh number of the filler matrix is 70-150, the wire diameter is 0.07-0.12 mm, the wire cloth thickness is 0.2-0.5 mm, the peak height is 2-15 mm, and the wave distance is 4-30 mm; And / or, the filler matrix is made of metal and / or plastic, preferably metal.
8. The method according to claim 6 or 7, wherein: In step (1), the thickness of the silane layer is 7-12 nm; And / or, the silanization treatment includes: contacting and immersing the solution containing the silane component with the outer surface of the filler matrix, and then drying and curing; And / or, in step (1), the solution containing the silane component is obtained by mixing a silane reagent, water and a low-carbon alcohol and pre-hydrolyzing them; Preferably, the volume ratio of silane reagent: water: low carbon alcohol is (2.2-5.2): (3.5-5.9): (89-95); Preferably, the silane reagent is selected from at least one of 2-butenyltriethoxysilane, methylvinyldiethoxysilane and allyldimethoxysilane.
9. The method according to claim 6 or 7, wherein: Based on the surface area of the filler matrix per square meter of dry basis, the content of pyrrole in the modified layer A is 13-23 mmol / m 2 The content of amide group is 18-38mmol / m 2 The furanyl content is 2.2-5.9mmol / m 2 ; And / or, in step (2), the thickness of the modified layer A is 4.5-8.2 nm.
10. The method according to claim 6 or 7, wherein: In step (2), the modification A treatment comprises: immersing a solution containing the modification component A into contact with the outer surface of the filler coated with the silane layer in step (1); And / or, in step (2), the solution containing modified component A comprises modified component A, a first initiator and a first solvent, wherein the mass ratio of modified component A: first initiator: first solvent is (4.5-7.9): (0.1-0.4): (93-97); And / or, in step (2), the first solvent is selected from at least one of toluene, p-xylene, m-xylene and o-xylene; And / or, in step (2), the first initiator is selected from at least one of azo, organic peroxide, inorganic peroxide and redox initiators, preferably at least one of azobisisobutyronitrile, benzoyl peroxide, potassium persulfate and hydrogen peroxide, more preferably benzoyl peroxide; And / or, in step (2), the modified component A contains pyrrole derivatives, amide derivatives, and furan derivatives, wherein the molar ratio of pyrrole derivatives: amide derivatives: furan derivatives is (15-27): (21-44): (2.7-6.8); and / or, the pyrrole group is provided by a pyrrole derivative, preferably provided by at least one of 3-isopropenyl-1-methyl-pyrrole, 1-(3-butene-1-yl)-2-vinyl-1H-pyrrole and 5-allyl-4-methoxy-1,5-dihydro-2H-pyrrol-2-one; and / or, the amide group is provided by an amide derivative, preferably provided by at least one of N,N'-dihydroxyethylbisacrylamide, N,N-methylenebisacrylamide and hexamethylenebisacrylamide; and / or, the furanyl group is provided by a furan derivative, preferably 2-(1-propen-2-yl)furan and / or 2-(2-pentenyl)furan; And / or, in step (2), the conditions of the modified A treatment include: liquid-to-solid volume ratio of 1-3, treatment temperature of 60-80°C, and treatment time of 1.5-3h.
11. The method according to claim 6 or 7, wherein: Based on the surface area of the filler matrix per square meter of dry basis, the content of phenoxy in the modified layer B is 13-24 mmol / m 2 The content of pyrrolyl is 19-36mmol / m 2 The furanyl content is 3.2-8mmol / m 2 The content of sulfonic acid group is 25-47mmol / m 2 The content of phosphate group is 8.7-24.5mmol / m 2 The content of amide group is 12-19mmol / m 2 ; And / or, the thickness of the modified layer B is 12-20 nm.
12. The method according to claim 6 or 7, wherein: In step (3), the modification B treatment comprises: immersing a solution containing the modification component B in contact with the outer surface of the filler coated with the modification layer A in step (2); And / or, in step (3), the solution containing modified component B contains modified component B, a second initiator and a second solvent, wherein the mass ratio of modified component B: second initiator: second solvent is (5.5-10.4): (0.1-0.5): (92-96); And / or, in step (3), the modified component B contains phenoxy derivatives, pyrrole derivatives, furan derivatives, sulfonic acid derivatives, phosphoric acid derivatives, and amide derivatives, wherein the molar ratio of phenoxy derivatives: pyrrole derivatives: furan derivatives: sulfonic acid derivatives: phosphoric acid derivatives: amide derivatives is (15-29): (22-43): (3.9-9.5): (30-56): (10.3-28.9): (14.3-22.7); And / or, the phenoxy group is provided by a phenoxy derivative, preferably provided by at least one of 4-methoxystyrene, allylphenyl ether and phenyl vinyl ether; and / or, the phosphate group is provided by a phosphate derivative, preferably by at least one of (2-fluoro-3,7-dimethylocta-1,6-dien-3-yl)phosphonyl hydrogen phosphate, [2-methyl-2-(4-methylpent-3-enyl)cyclopropyl]methylphosphonyl hydrogen phosphate and 2-(phosphoryloxy)propane-1,3-diyl dimethacrylate; and / or, the sulfonic acid group is provided by a sulfonic acid derivative, preferably by at least one of 4-hydroxy-6-(prop-2-enoylamino)naphthalene-2-sulfonic acid, (Z)-4',4"'-(ethylene-1,2-diyl)bis(([[1,1'-biphenyl]-4-sulfonic acid)) and 4-{(E)-2-[3,5-di(sulfooxy)phenyl]vinyl}phenyl hydrosulfate; And / or, in step (3), the conditions for the modified B treatment include: liquid-to-solid volume ratio of 1-3, treatment temperature of 70-90° C., and treatment time of 1.5-3 h.
13. The method according to claim 12, wherein: Step (3) further comprises subjecting the modified B-treated product to post-modification treatment in a post-modification treatment agent; and / or, the modified post-treatment agent is selected from at least one of ethanol, acetone and methanol, preferably ethanol; And / or, the post-modification treatment conditions include: treatment time of 0.5-1h; Preferably, the post-modification treatment further comprises drying the post-modification treatment product; Preferably, the drying conditions include: a drying temperature of 100-120° C. and a drying time of 0.5-1 h.
14. Use of the modified hydrated filler according to any one of claims 1 to 5 or the modified hydrated filler prepared by the preparation method according to any one of claims 6 to 13 in the preparation of low-carbon alcohol aqueous solution by hydration reaction of low-carbon olefins.
Citation Information
Patent Citations
Dental repair composite resin with biological activity and preparation method thereof
CN113648228A
Denitrification filler and sewage treatment method thereof
CN115477396A
Desulfurization filler as well as preparation method and application thereof
CN115957589A
Dealkalization refining agent as well as preparation and application thereof
CN115957590A
Treatment Of Filler With Silane
US20140350152A1
Cited By
Modified hydrolyzed filler, preparation method and application thereof, and preparation method of formaldehyde formic acid aqueous solution
CN117920341A
Modified hydrolyzed fillers, their preparation methods and applications, and methods for preparing formaldehyde-formic acid aqueous solutions.
CN117920341B
Low-carbon olefin hydration product separation fiber membrane as well as preparation method and application thereof
CN119656876A
A low-carbon olefin hydration product separation fiber membrane and a preparation method and application thereof
CN119656876B